(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Management of map layers plays a crucial role in the fields of geodesy and Geographic Information Systems (GIS). Geodesy ensures the accuracy of map layers by studying the shape and measurements of the Earth’s surface, which enables the storage, analysis, and visualization of data through GIS systems. The process of managing map layers involves organizing data for use in various fields such as urban planning, ecology, and transportation. This topic provides an in-depth analysis of the interrelationship between geodesy and GIS systems and explores best practices for improving the management of map layers.